Deformable liposomes by reverse-phase evaporation method for an enhanced skin delivery of (+)-catechin. (February 2014) - Chen, Guanyu; Li, Danhui; Jin, Ye; Zhang, Weiyu; Teng, Lirong; Bunt, Craig; Wen, Jingyuan
Abstract Background: (+)-catechin, as the most common catechin isomer, is recognized to be an antioxidant which benefits the skin in many ways. The purpose of the present study was to prepare and evaluate a suitable liposomal delivery systems for (+)-catechin topical application. Methods: In this study, catechin-loaded conventional liposomal delivery system, deformable conventional liposomal delivery system and deformable liposomes prepared by reverse-phase evaporation (REV) method were compared. The three systems were characterized for liposome particle size, zeta-potential, entrapment efficiency, drug release, permeability across porcine skin and catechin deposition in the skin. Results: It was revealed that the size of deformable conventional liposomes before freeze-drying and deformable REV liposomes after freeze-drying range from 335.6 ± 71.7 nm to 551.1 ± 53.4 nm, respectively, which were considered to be suitable for skin delivery. The deformable REV liposomes had a higher aqueous volume and thus were able to entrap greater amounts of hydrophilic (+)-catechin (50.0 ± 5.9%) compared to conventional (30.0 ± 3.8%) and deformable conventional liposomes (36.1 ± 4.6%). All liposomal formulations exhibited a prolonged catechin release. Compared to deformable liposomes, the REV deformable liposomes showed a significantly better deposition of (+)-catechin while catechin solution did not permeate into the porcine ear skin. Conclusion: Among all formulations studied, deformable REV liposomes were considered to be favorable for catechin topical delivery.